Visual Narrative through Motion Lines and Speed Lines: A Case Study of Contemporary 3D Animation - Troy; Muhammad Adlan (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
The development of 3D animated movies has adapted visual elements of comics, such as motion lines and speed lines, into digital media, but there has been no study that combines visual semiotics, narrative functions, and the transformation of comic styles into 3D animated movies. The purpose of this study is to map the semiotic mechanisms and dramatic functions of motion lines and speed lines through case studies of three movies, including Spider-Man: Across the Spider-Verse (2023), Puss in Boots: The Last Wish (2022), and The Bad Guys (2022). The method used is a descriptive qualitative approach: visual semiotics analysis to unravel denotative and connotative meanings, as well as narrative analysis to map the effects' contribution to the rhythm, conflict, and climax of the story. The results show that motion lines and speed lines operate in two ways: as markers of movement that communicate kinetic intensity, and as narrative devices that reinforce dramatic rhythm and audience affect. These effects also create an aesthetic hybridity between comics and cinema, providing an additional layer of interpretation that enhances affective engagement and dramatic understanding. This research provides theoretical and practical contributions to the study of visual semiotics and digital animation narrative design.